Moving from English-Indonesia language mixing in Elementary school to bilingual classroom - Sagala, Rakhmat Wahyudin; Siregar, Febri Dayani; Lubis, Rahmadani; Juriah; Rangkuti, Nabila Humairah (Journal of Elementary School Education, 2023)
This study discusses learning activities that combine Indonesian and English simultaneously in each lesson. Ultimately, it is recommended to become a bilingual class in elementary schools. Implementing bilingual classes refers to the 2005 Government Regulation, the 2006 Minister of Education Decree—the 2013 Minister of Education and Culture Regulation concerning Graduate Competency Standards (SKL). Data were obtained by convenience sampling of 34 students and teachers at the Muhammadiyah 21 Elementary School in Medan. The ultimate goal of this study was to determine bilingual learning on students' learning motivation. The results of the study state that there are advantages and disadvantages to bilingual learning. Challenges in this study mention the limitations of teachers teaching bilingual learning. In addition, facilities and infrastructure for bilingual learning are minimal. While the strength is that students have more competence by mastering bilingual material, students are able to improve critical thinking.